Dairy Whey Proteins and Obesity - Pal, Sebely; Radavelli-Bagatini, S.; Ho, S.; McKay, J.; Hagger, Martin; Jane, M. (Elsevier Inc., 2014)
Studies show that whey protein and its bioactive components can promote greater health benefits compared to other protein sources such as egg and casein. The aim of this chapter is to review the effects of whey protein on metabolic syndrome risk factors. Consumption of whey protein has been shown to improve glucose levels and insulin response, promote a reduction in blood pressure, improve vascular function, and improve the lipid profile. The collective view of the current scientific evidence is that the consumption of whey protein may have beneficial effects on some symptoms of metabolic syndrome, as well as reducing cardiovascular risk factors. © 2014 Elsevier Inc. All rights reserved.